Nilai-Nilai Pendidikan Karakter yang Terkandung Dalam Khazanah Leksikon Istana Raja Sumbawa (Dalam Loka) di Kabupaten Sumbawa: Menemukan Model Baru Penguatan Karakter Berbasis Kearifan Lokal - Hermansyah, Wawan; Gunawan, Hendra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research tried to find the values of local wisdom in the lexicon treasures of Raja Sumbawa Palace (Dalam Loka) which was further directed to be a model in strengthening character education. Character education is expected to be contained in formal, non-formal and informal educational activities in Sumbawa Regency. Of course by considering the mechanisms and procedures that apply, for example by reviewing the local curriculum content in elementary and secondary schools. There are two main theories used by researchers in developing research directions, namely anthropolinguistic theory and social semiotics. This research is qualitative descriptive, which seeks to describe systematically, factually and accurately about the facts about various lexicon in the Palace of King Sumbawa (In Loka). Data is obtained from observations, interview results, shooting results, document analysis and field records. Data in the analysis with three stages, namely; Presentation of data, stage of data comparation, and stage of presentation of research results. The results of this study found, 20 forms of lexicon contained in the Palace of King Sumbawa (In Loka). Of the 20 Lexicon can represent seven (7) forms of character education from eighteen values developed in character education.